Migrations of Chinese to Costa Rica and its consequent process Of assimilation since 1855 - Sai Acón, Lai (2016)
Exploring identity issues in the Chinese community of Costa Rica and outlining migratory movements of Chinese people toward and within Costa Rica are key to understand assimilation processes of first-wave immigrants and their descendants. As the Chinese experience in Costa Rica is anything but singular, this article sets out to reconstruct the history of the Chinese community with several approaches:  archival research, interviews with descendants of Chinese immigrants, and personal experience as a member of the community.